PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN CANVA TERHADAP KETERAMPILAN MENULIS TEKS IKLAN SISWA KELAS VIII SMPN 1 PANTAI CERMIN - Amatillah, Fitri Yati; Zulfikarni; Anggraini, Dewi; Fella Henanggil, Mita Domi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Advertisement writing is one of the productive language skills that junior high school students are expected to master. However, many students still encounter difficulties in developing ideas, using persuasive language, and creating visually appealing advertisement designs. This study aimed to determine the effect of the Project Based Learning (PjBL) model assisted by Canva on the advertisement writing skills of eighth-grade students at SMPN 1 Pantai Cermin. This study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The sample consisted of 30 students selected through purposive sampling. The research instrument was a performance test in advertisement writing, which was assessed based on four indicators: text structure, visual and design, linguistic features, and the use of Indonesian spelling conventions. Data were analyzed using the t-test to examine the differences in students' writing skills before and after the treatment. The findings revealed that the students' advertisement writing skills improved after the implementation of the Project Based Learning model assisted by Canva. The mean score increased from 70.41, categorized as More than Adequate, before the treatment to 90.83, categorized as Very Good, after the treatment. The hypothesis testing also indicated that the implementation of the Project Based Learning model assisted by Canva had a significant effect on students' advertisement writing skills. Therefore, the Project Based Learning model assisted by Canva can be considered an innovative instructional alternative to enhance students' creativity and advertisement writing skills in Indonesian language learning.